2012
DOI: 10.1038/ja.2012.10
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of madurastatin C1, a novel siderophore from Actinomadura sp.

Abstract: Actinomycetes are known for their large genetic potential to produce several distinct classes of secondary metabolites. 1 While cultivating Actinomadura sp. DSMZ 13491, the producer of the cyclic heptapeptide GE23077, 2 we observed it produced an antibacterial activity. Despite being a potent and selective inhibitor of bacterial RNA polymerase, GE23077 is devoid of activity against bacterial cells, except for marginal activity against some Moraxella spp. 2 Here we report on the isolation, structure elucidation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
27
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 9 publications
2
27
0
Order By: Relevance
“…At rst, a new tetrasaccharide derivative, actinotetraose L (28), was discovered by Guo et al But the compound was not shown to display potent immunosuppressive activity and cytotoxicity from T-cell viability and MTT assays. 16 One new angucyclinone derivative, amycomycin A (29), and one new angucycline, amycomycin B (30), along with 5 known compounds, tetrangomycin (31), PD116779 (32), X-14881E (33), sakyomicin A (34) and sakyomicin C (35), also were isolated from the rare actinobacterium Amycolatopsis sp. HCa1.…”
Section: Introductionmentioning
confidence: 99%
“…At rst, a new tetrasaccharide derivative, actinotetraose L (28), was discovered by Guo et al But the compound was not shown to display potent immunosuppressive activity and cytotoxicity from T-cell viability and MTT assays. 16 One new angucyclinone derivative, amycomycin A (29), and one new angucycline, amycomycin B (30), along with 5 known compounds, tetrangomycin (31), PD116779 (32), X-14881E (33), sakyomicin A (34) and sakyomicin C (35), also were isolated from the rare actinobacterium Amycolatopsis sp. HCa1.…”
Section: Introductionmentioning
confidence: 99%
“…24,7,8,10,1317,29,52–70 Likewise, including the new bacterial carboxamides 6 and 7 reported herein, over 60 benzamide derivatives have been reported from bacteria, many of which also reportedly display interesting biological and pharmaceutical properties. 71 Importantly, the current study is the first to assess spoxazomicins or oxachelins in the context of neuroprotection against EtOH-induced damage, where corresponding bioactivity comparisons among the analogues tested highlight the importance of the spoxazomicin D ( 2 ) carboxamide and oxachelin C ( 5 ) salicylate as critical to this newly discovered function.…”
Section: Resultsmentioning
confidence: 76%
“…Roughly 0.3% 1 of reported microbial metabolites are classified as phenol-oxazolines or salicylate-containing natural products, where salicylate C7 amino acid or peptide modification is a common feature (e.g., spoxazomicins, 2,3 oxachelin, 4,5 amychelin, 6 madurastatins, 7,8 acinetobactin, 9 asterobactins, 10 carboxymycobactins, 1113 exochelins, 14 and nocardimicins 15,16 ). While most commonly reported as metal chelators/siderophores, 4,6,10 representative members have also been noted to display cancer cell line cytotoxicity and antimicrobial and antitrypanosomal activities.…”
mentioning
confidence: 99%
“…For macrocyclization, a hydroxyl or an amino group of the acyl or peptidyl chain acts as an internal nucleophile to attack the carbonyl carbon of the acyl or peptidyl-O-TE and a cyclic product is released. Typically, the nucleophile is in an amino acid earlier in the peptide chain (Du and Lou, 2010), but recently, a number of siderophores have been isolated that have either a C-terminal cyclic N d -OH-ornithine (Kodani et al, 2013;Mazzei et al, 2012;Seyedsayamdost et al, 2011) or a C-terminal cyclic N ε -OH-lysine (Hoshino et al, 2011). In these cases, the hydroxylamine of the C-terminal N d -OH-ornithine or N ε -OH-lysine is thought to be used as a nucleophile to generate small, N-heterocycles and release linear peptides.…”
Section: Discussionmentioning
confidence: 99%